2022
DOI: 10.12998/wjcc.v10.i9.2883
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar disc sequestration mimicking a tumor: Report of four cases and a literature review

Abstract: BACKGROUND Disc herniation refers to the displacement of disc material beyond its anatomical space. Disc sequestration is defined as migration of the herniated disc fragment into the epidural space, completely separating it from the parent disc. The fragment can move in upward, inferior, and lateral directions, which often causes low back pain and discomfort, abnormal sensation, and movement of lower limbs. The free disc fragments detached from the parent disc often mimic spinal tumors. Tumor like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…From literature review, it was shown that evidence of peripherally enhanced lesion in a contrast enhanced MRI may indicate presence of intervertebral disc, however in our case, peripheral enhancement was not seen [7]. Hence, absence of this criteria should not rule out presence of intervertebral disc.…”
Section: Histopathological Examinationmentioning
confidence: 52%
See 1 more Smart Citation
“…From literature review, it was shown that evidence of peripherally enhanced lesion in a contrast enhanced MRI may indicate presence of intervertebral disc, however in our case, peripheral enhancement was not seen [7]. Hence, absence of this criteria should not rule out presence of intervertebral disc.…”
Section: Histopathological Examinationmentioning
confidence: 52%
“…The surgical outcome of our case is good with the patient able to regain full power of his lower limbs. Literature review also showed similar outcomes [2], [7], [8]. Thus, we suggest for prompt surgical intervention despite diagnostic dilemma, to ensure good prognosis.…”
Section: Histopathological Examinationmentioning
confidence: 55%
“…Diagnosing large LDH may be challenging, and severe disc herniation often mimics spinal tumors [ 6 - 10 ]. Thorough medical history, clinical features, physical examination, and radiological examinations such as an MRI or computed tomography are also used to diagnose and evaluate the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing large LDH may be challenging, and severe disc herniation often mimics spinal tumors [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…특징적으로 신경초종은 종종 T2 강조영상에서 중심부 저신호강도와 주변부 고신호강도를 보이는 ‘표적 징후(target sign)’를 나타낸다. 이는 분리추간판 조각과는 반대되는 소견으로 주요 감별점이 될 수 있다( 41 ). 그러나 신경초종이 중심부에서 낭성변성을 보이는 경우에는 감별이 어려울 수 있다.…”
Section: 분리디스크와 감별해야 하는 척추질환unclassified